Molecular and functional characterization of cDNAs putatively encoding carboxylesterases from the migratory locust, Locusta migratoria - Zhang, Jianqin; Li, Daqi; Ge, Pingting; Guo, Yaping; Zhu, Kun Yan; Ma, Enbo; Zhang, Jianzhen (My University, 2014)
Carboxylesterases (CarEs) belong to a superfamily of metabolic enzymes encoded by a number of genes and are widely distributed in microbes, plants and animals including insects. These enzymes play important roles in detoxification of insecticides and other xenobiotics, degradation of pheromones, regulation of neurodevelopment, and control of animal development. In this study, we characterized a total of 39 full-length cDNAs putatively encoding different CarEs from the migratory locust, Locusta migratoria, one of the most severe insect pests in many regions of the world, and evaluated the role of four CarE genes in insecticide detoxification. Our phylogenetic analysis grouped the 39 CarEs into five different clades including 20 CarEs in clade A, 3 in D, 13 in E, 1 in F and 2 in I. Four CarE genes (LmCesA3, LmCesA20, LmCesD1, LmCesE1), representing three different clades (A, D and E), were selected for further analyses. The transcripts of the four genes were detectable in all the developmental stages and tissues examined. LmCesA3 and LmCesE1 were mainly expressed in the fat bodies and Malpighian tubules, whereas LmCesA20 and LmCesD1 were predominately expressed in the muscles and hemolymph, respectively. The injection of double-stranded RNA (dsRNA) synthesized from each of the four CarE genes followed by the bioassay with each of four insecticides (chlorpyrifos, malathion, carbaryl and deltamethrin) increased the nymphal mortalities by 37.2 and 28.4% in response to malathion after LmCesA20 and LmCesE1 were silenced, respectively. Thus, we proposed that both LmCesA20 and LmCesE1 played an important role in detoxification of malathion in the locust. These results are expected to help researchers reveal the characteristics of diverse CarEs and assess the risk of insecticide resistance conferred by CarEs in the locust and other insect species.
Citation: Zhang J, Li D, Ge P, Guo Y, Zhu KY, et al. (2014) Molecular and Functional Characterization of cDNAs Putatively Encoding Carboxylesterases from the Migratory Locust, Locusta migratoria. PLoS ONE 9(4): e94809. doi:10.1371/journal.pone.0094809
Keywords: Carboxylesterases; cDNAs; Locusta migratoria; Migratory locust